ASSOCIATION OF PREMENTRUAL SYNDROME TO STRESS INCIDENT AMONG XI GRADERS IN YOGYAKARTA, INDONESIA - Ajeng Maharani Pratiwi; Erinda Nur Pratiwi; Dheby Kurnia Utami; Pratiwi Puji Lestari (Proceedings of the International Conference on Applied Science and Health, 2017)
Background: Menstruation is the blood loss that occurs periodically through the vagina comes from the uterine wall. The discomfort of women before, during and after menstruation the women usually feel discomfort or it is called premenstrual syndrome. The incidence of premenstrual syndrome in Indonesiais about 23%. Premenstrual Syndrome was disturbing about 30-40% of women reproductive age. Aims: The aim of this study to identify existing correlation stress premenstrual syndrome female adolescent girls of XI grade in SMK X Yogyakarta Indonesia. Methods: This study is a descriptive analytic design with cross sectional. This study population involved 82 students was using purposive sampling. The instrument was a questionnaire to measure the presence or absence of stress and premenstrual syndrome. The data analysis was used chi square. Results: The level of stress in women adolescents mostly in the mild category 48 (58.5%), the incidence of premenstrual syndrome in adolescents in the category of pre menstruation syndrome (PMS) is 58 (70.7%) and in this study no experience severe stress and very heavy. Students with mild stress who experience premenstrual syndrome were 39 (47.6%), while students with moderate stress experienced premenstrual syndrome were 19 (23.2%). The results of the analysis using Chi-Square showed that the relationship between stress and the incidence of premenstrual syndrome in young women in the category of weak. Conclusion: There is no relationship between stress and the incidence of premenstrual syndrom in girl adolescents of XI grade in SMK X Yogyakarta Indonesia